Velocidade da barra como medida da intensidade da carga nos exercícios agachamento livre e deadlift com barra hexagonal - Santos, Petrus Gantois Massa Dias dos (2022)
Velocity-based training (VBT) approach has been increasingly implemented by strength and conditioning coaches due to its practical advantages in daily prescribing and adjustment of resistance exercise loads compared to traditional models based on the percentage of one-repetition maximum (1RM) and the maximum number of repetitions (MNR). One of the assumptions of this velocity-approach relies on the negative and very strong relationship between movement velocity and their respective submaximal loads, which allows estimating with high accuracy the resistance exercise loads. However, to properly implement the VBT approach, it is necessary to investigate the accuracy of the load-velocity relationship in estimating the resistance exercise loads in those exercises commonly incorporated during resistance training (RT) programs. Despite the literature has already demonstrated the effectiveness of the load-velocity relationship in several resistance exercises, its accuracy to estimate the load during free-weight back-squat and hexagonal bar deadlift exercises is still unknown. Therefore, this thesis aimed to investigate the accuracy of different methods based on the load-velocity and load-power to estimate the load during free-weight back-squat and hexagonal bar deadlift exercises. For that, the thesis was divided into three studies. A systematic review study was conducted to determine the accuracy of the load-velocity relationship in several resistance exercises and to identity possible gaps in the literature on VBT. In studies 2 and 3, twenty-five resistance-trained men performed a progressive load test up to 1RM to determine the full load-velocity relationship during the free-weight back-squat and deadlift exercises. The 1RM assessment was carried out on non-consecutive days (~1 week) in a random order of presentation. In study 2, the general load-velocity relationship was determined in both exercises. A negative and very strong relationship between movement velocity and the relative load was found for both back-squat (R2 = 0.96) and deadlift (R2 = 0.97) exercises. The load that maximizes the mechanical power output in the back-squat was ~65% 1RM and in the deadlift was ~60% 1RM. Bland-Altman plot reported high agreement level between actual and predicted 1RM during the back-squat (ICC = 0.97; CI95% = 0.93 to 0.99) and deadlift (ICC = 0.981; IC95% = 0.83 to 0.99) exercises. In study 3, it was analyzed the effects of a different number of submaximal loads on the accuracy of 1RM prediction based on the individual load-velocity relationship in both exercises. The 1RM was accurately predicted, regardless of the number of loads used (2-, 3-, 4-, and 6-points) (absolute error < 7.0 kg; ES < 0.25; trivial to small). In conclusion, the VBT paradigm can be implemented by strength and conditioning coaches to accurately prescribe the load during the free-weight back-squat and hexagonal bar deadlift exercises in resistance-trained men.